SO3H-functionalized mesoporous silica materials as solid acid catalyst for facile and solvent-free synthesis of 2H-indazolo[2, 1-b]phthalazine-1, 6, 11-trione derivatives. (12th October 2015) - Alinasab Amiri, Ali; Javanshir, Shahrzad; Dolatkhah, Zahra; Dekamin, Mohammad G.
Abstract : SO3 H-functionalized mesoporous silica materials were used to synthesize 2 H -indazolo[2, 1- b ]phthalazine-1, 6, 11-trione derivatives in a one-pot three-component condensation reaction. Abstract : SO3 H-functionalized mesoporous silica materials (SO3 H-FMSM), as an efficient, mild, recoverable and environmentally friendly heterogeneous mesoporous nanocatalyst, was used to synthesize 2 H -indazolo[2, 1- b ]phthalazine-1, 6, 11-trione derivatives in a one-pot three-component condensation reaction of 2, 3-dihydrophthalazine-1, 4-dione, dimedone, and benzaldehyde derivatives under thermal solvent-free (SF) conditions in excellent yields and short reaction times.